2015
DOI: 10.3109/0886022x.2015.1040337
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation is associated to volume status in peritoneal dialysis patients

Abstract: Aim: The aim of this study is to investigate whether there is a relationship between inflammation and volume status in patients underwent peritoneal dialysis (PD). Patients and method: This cross-sectional study included 159 PD patients. The median duration of PD was 17 (range, 1-151) months. All patients were examined using bioelectrical impedance analysis to estimate the ratio of extracellular water to total body water (ECW/TBW), which was used to assess their volume status. The patients were categorized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In PD patients, the same pattern of correlation has been reported 108,109,116,117 . For example, CRP levels were significantly increased in hypervolemic PD patients, and the severity of fluid overload 117,118 . Similarly, serum IL‐6 levels correlated with overhydration and NT‐pro‐BNP levels in PD patients 119 …”
Section: Inflammation and Fluid Overloadsupporting
confidence: 57%
See 1 more Smart Citation
“…In PD patients, the same pattern of correlation has been reported 108,109,116,117 . For example, CRP levels were significantly increased in hypervolemic PD patients, and the severity of fluid overload 117,118 . Similarly, serum IL‐6 levels correlated with overhydration and NT‐pro‐BNP levels in PD patients 119 …”
Section: Inflammation and Fluid Overloadsupporting
confidence: 57%
“…108,109,116,117 For example, CRP levels were significantly increased in hypervolemic PD patients, and the severity of fluid overload. 117,118 Similarly, serum IL-6 levels correlated with overhydration and NT-pro-BNP levels in PD patients. 119 The pathogenic link between fluid overload and inflammation is an active area of research.…”
Section: Inflammation and Fluid Overloadmentioning
confidence: 92%
“…It is well known, inter-alia on the basis of many studies with dialyzed subjects, that there is a strict correlation between the inflammation involving TNFα, IL-1β, IL-6 and MMPs and hydration changes [9][10][11]. In a cross-sectional study, including 159 patients subjected to peritoneal dialysis, Unal et al [19] demonstrated that in hypervolemic patients compared with euvolemic patients, hs-CRP value levels were significantly higher. The ECW/TBW ratio positively correlated with hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, through trajectory modeling and correlation analysis, we observed that the high ECW/TBW trajectory group showed a slow and sustained elevated course of change in the trend from 1 to 7 days of admission. The sustained increase in ECW/TBW may reflect a loss of muscle mass [ 24 ]. Meanwhile, a study by Unal A [ 24 ]et al noted that the ECW/TBW ratio was positively correlated with the inflammatory index hypersensitivity C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the intensive care unit (ICU) setting, PA and ECW/TBW are associated with worse clinical outcomes such as mortality rate and length of ICU stay [ [20] , [21] , [22] ]. In addition, PA and ECW/TBW are also considered to be closely related to nutritional and inflammatory status, serving as comprehensive indicators that can simultaneously reflect both states [ 23 , 24 ]. However, previous studies have mostly focused on the relationship between the measurement values of these indicators at a given moment and prognosis, failing to continuously measure and dynamically assess changes in clinical status.…”
Section: Introductionmentioning
confidence: 99%